Direct and Inverse Results for Kantorovich Type Exponential Sampling Series - Angamuthu, Sathish Kumar; Bajpeyi, Shivam (Resultate der Mathematik, 2020)
In this article, we analyse the behaviour of the new family of Kantorovich type exponential sampling series. We derive the point-wise approximation theorem and Voronovskaya type theorem for the series ( I w χ ) w > 0 . Further, we establish a representation formula and an inverse result of approximation for these operators. Finally, we give some examples of kernel functions to which the theory can be applied along with the graphical representation.